Gustav Amsinck. Ein Hamburger Großkaufmann in New York - Rheinholz, Constanze (Mäzene für Wissenschaft, 2011)
In 1857, the young Hamburg merchant Gustav Amsinck set off for the United States. In the booming metropolis of New York, he expanded his brother's "goods commission and banking business" with skill, diligence and a wealth of ideas. Under his aegis, G. Amsinck & Co. survived revolts in South America, attempts to defraud, and shipwrecks. In addition to its core business which consisted especially of sugar and coffee trading the merchant banker also invested in new barrel tyre patents, prefabricated houses and was involved in the construction of the Panama Canal. Privately, Gustav Amsinck appreciates the beautiful arts and traveling. When the Hamburgische Wissenschaftliche Stiftung came into being in 1907, he was one of its most important donors. This biography traces the rise of this man, who achieved prestige and wealth with Hanseatic merchants' virtues in the land of unlimited possibilities.